Blind-Walking Behavior in the Dark Affected by Previewing the Testing Space. (November 2019) - Kelly, Susan A.
Visual environments affect egocentric distance perceptions in full cue conditions. In this study, the effect of three spatial layouts was tested on the perceived location of a self-illuminated single target viewed in the dark. Blind-walking (BW) estimates of target distance were underestimated in all testing spaces, as expected, but foreshortened significantly more in the shortest of the three testing rooms. Additional experiments revealed that neither changes in the perceived angle of declination nor perceived eye height were responsible for this effect. The possibility that subjects made cognitive adjustments to BW behavior to reduce physical risk was assessed by remeasuring target locations in the three different locations with magnitude estimation and by comparing the BW results obtained from subjects who had no preview of the testing space with those who had. The results support the conclusion that the effect of spatial layout is likely due to cognitive adjustments to BW behavior. The results also indicate that the perceived angle of declination is always overestimated by at least a factor of 1.5. These results can be interpreted within the context of a theory of space perception called the angular expansion theory (AET).